Outcomes After Human Papillomavirus Vaccination in Patients With Recurrent Respiratory Papillomatosis: A Nonrandomized Clinical Trial - Smahelova, Jana; Hamsikova, Eva; Ludvikova, Viera; Vydrova, Jitka; Traboulsi, Joseph; Vencalek, Ondrej; Lukeš, Petr; Tachezy, Ruth (JAMA otolaryngology - head & neck surgery, 2022)
Importance: Recurrent respiratory papillomatosis (RRP) is a rare benign chronic disease of the larynx etiologically linked with the infection of low-risk human papillomavirus (HPV). Combination of surgical and immunomodulatory therapy has limited success. Possible use of prophylactic HPV vaccine that includes HPV-6 and HPV-11 antigens has been studied. Objective: To evaluate if the HPV vaccination is associated with a lower number of recurrences requiring surgical intervention in patients with new and recurrent RRP. Design, Setting, and Participants: This was a non-placebo-controlled intervention study. Enrollment data were collected from October 2011 to August 2013. The patients were followed up at 1 month, 12 months, and 5 years after the third dose of the vaccine and clinically monitored until December 31, 2018. Data were analyzed from 2019 to 2021. Altogether, 50 adults with active RRP were enrolled and followed up in referral centers. For the final outcome, follow-up data for 42 patients were available. Eight patients who did not fulfill the protocol were excluded. Interventions: All patients received HPV vaccine as an adjuvant treatment and were clinically followed up. When RRP progression or a significant recurrent lesion was detected, surgical removal via direct laryngoscopy was indicated. No adjuvant therapy with antiviral or biological agents was used. Main Outcomes and Measures: This study compared the prevaccination and postvaccination positivity for HPV-specific antibodies. The main outcome was the difference in the frequency of RRP recurrences in the prevaccination and postvaccination period. Results: A total of 50 patients with RRP were enrolled (median [SD] age, 41.5 [12.3] years [range, 21-73 years]; 39 [78%] men and 11 [22%] women). After HPV vaccination, patients with previously no HPV-specific antibodies showed seroconversion, and all patients developed 100-fold higher levels of HPV vaccine type-specific antibodies compared with the prevaccination period. In patients with recurrent RRP, decreased frequency of recurrences requiring surgical treatment was present after vaccination (from 0.85 to 0.36 recurrences/y). No difference in postvaccination recurrences was found between patients with newly diagnosed and recurrent RRP. Conclusions and Relevance: In this nonrandomized clinical trial, the frequency of RRP recurrences was significantly lower after HPV vaccination, and patients with RRP thus had a reduced burden of disease. Because no difference was detected in the frequency of recurrent postvaccination lesions in patients with new and recurrent disease, it appears that both groups showed equal benefit following HPV vaccination. These findings suggest that the earlier that patients with RRP receive HPV vaccine, the sooner they may show reduced burden of disease. Trial Registration: EudraCT Identifier: 2011-002667-14; ClinicalTrials.gov Identifier: NCT01375868.
Keywords: infekce dýchací soustavy; vakcinace; dospělí; Papillomavirus Vaccines; Alphapapillomavirus; lidé; Female; Papillomavirus Infections; mužské pohlaví; vakcíny proti papilomavirům; Vaccination; Male; Respiratory Tract Infections; Adult; ženské pohlaví; infekce papilomavirem; Humans